HOW MIND MAPPING TECHNIQUE EFFECTIVE ON STUDENTS’ DESCRIPTIVE WRITING ACHIEVEMENT - Jelimun, Maria Olga (Universitas PGRI Sumatera Barat, 2024)
This study aims at analyzing the effectiveness of the mind mapping technique on students’ descriptive writing achievement. This research belongs to quasi experiment. The population was tenth grade of SMKN Mano, East Manggarai Regency, NTT, Indonesia. The sample was two classes consisting of 72 students. The instrument used was writing test and the data were analyzed quantitively and qualitatively. The result shows that the use of mind mapping technique in teaching writing was effective regarding the students’ descriptive writing achievement. It had been proved through the average scores from the pre-test and the post-test scores in experimental class, where the pre-test scores was 65,6944 to 82,5277 in the post test. It is also supported by the total number of students with a very good writing category. There were 22 from 36 students who have better score writing achievement (“very good” writing category) after using mind mapping technique in their writing. While 14 students left has a “good” and “fair” score writing achievement. Besides, based on the description of statistical tests in the experimental class shows that the value of tob < -tcv or it can be formulated -2,9248 < -1,99444 ( two tailed). It means that the use of mind mapping technique in teaching writing in tenth grade students in of SMKN Mano 1 was effective.